PENGARUH BERBAGAI JENIS BAHAN LITTER TERHADAP RESPON FISIOLOGIS BROILER FASE FINISHER DI CLOSED HOUSE - Anung Cahya Dewanti; Purnama Edy Santosa; Khaira Nova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This study aimed to: 1) determine the effect of the use of rice husk, rice straw and woodshavings as litter material on the physiological response of broiler finisher phase (14th days–harvest)in closed house, 2) determine the best type of litter material on the physiological response of broilerfinisher phase (14th days–harvest) in the closed house. This study was conducted over 26th days on15th April–10th May 2014 in closed house owned by PT. Rama Jaya Lampung Krawang Sari Village,Natar District, South Lampung regency. The design used was completely randomized design (CRD)with three treatments and six replications. The treatment consists of the type of litter material (ricehusk, wood shavings, straw and rice). Each experimental unit consisted of 15 birds and 18 plotsenclosure so broiler strain CP 707 is used as much as 270 tails. Sampling was conducted physiologicalresponses by 20% of the number of experimental units. The Data obtained was analyzed using a rangeof 5% significance level.Based on these results it can be concluded that: (1) the use of various types of litter materialson the physiological response of broiler did not significantly affect respiratory rate, heart rate, rectaltemperature and temperature shank, (2) there is no treatment of rice husk litter type material, shavingswood, and rice straw on the closed house best effect on respiratory rate, heart rate, rectal temperature,and temperature on broiler finisher phase shank.